Halal Labeling and Product Quality on Purchase Intention of Halal Food MSMEs: The Role of Consumer Trust as an Intervening Variable - Amalia Salsabila; Efi Syarifudin; Budi Sudrajat; Hadi Peristiwo; Suja'i Suja'i; Najmudin Najmudin (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
ABSTRACT Introduction: The halal industry has grown rapidly and has become an important sector in the global economy. Halal products are not only associated with religious obligations for Muslim consumers but are also considered indicators of product quality, safety, and credibility. This study aims to examine the effect of halal labeling and product quality on purchase intention of halal food Micro, Small, and Medium Enterprises (MSMEs), with consumer trust as an intervening variable. Methods: This research employs a quantitative approach using data collected from 100 respondents who have purchased or consumed halal food products from MSMEs. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results: Product quality significantly influences consumer trust, while halal labeling does not. However, halal labeling directly affects purchase intention. Product quality does not directly influence purchase intention but has an indirect effect through consumer trust. Consumer trust significantly affects purchase intention and mediates the relationship between product quality and purchase intention, but not between halal labeling and purchase intention. Conclusion and Suggestion: Product quality plays a key role in building consumer trust, which drives purchase intention, whereas halal labeling primarily acts as a direct cue in purchasing decisions. Therefore, halal food MSMEs should focus on maintaining product quality while ensuring credible halal certification.